2020
DOI: 10.1142/s0219061321500112
|View full text |Cite
|
Sign up to set email alerts
|

From noncommutative diagrams to anti-elementary classes

Abstract: Anti-elementarity is a strong way of ensuring that a class of structures, in a given first-order language, is not closed under elementary equivalence with respect to any infinitary language of the form L ∞λ. We prove that many naturally defined classes are anti-elementary, including the following: • the class of all lattices of finitely generated convex ℓ-subgroups of members of any class of ℓ-groups containing all Archimedean ℓ-groups; • the class of all semilattices of finitely generated ℓ-ideals of members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The papers [41] and [42] contain a deep study of the spectrum problem from a logical point of view. In [41] it is shown that second countable spectral spaces which are prime spectra of MV-algebras are characterized by a simple first order formula, whereas in [42] is is shown that no infinitary first order logic can express the prime spectra of MV-algebras. Other information is contained in [43].…”
Section: Introductionmentioning
confidence: 99%
“…The papers [41] and [42] contain a deep study of the spectrum problem from a logical point of view. In [41] it is shown that second countable spectral spaces which are prime spectra of MV-algebras are characterized by a simple first order formula, whereas in [42] is is shown that no infinitary first order logic can express the prime spectra of MV-algebras. Other information is contained in [43].…”
Section: Introductionmentioning
confidence: 99%